2017
DOI: 10.1007/s00535-017-1329-y
|View full text |Cite
|
Sign up to set email alerts
|

ALEX1, a novel tumor suppressor gene, inhibits gastric cancer metastasis via the PAR-1/Rho GTPase signaling pathway

Abstract: ALEX1 expression is reduced in GC and is involved in diverse cellular functions. ALEX1 inhibits metastasis through the PAR-1/Rho GTPase signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Fujimoto et al reported that PAR1 induced GC cells to become stem-like, inhibited yes-associated protein (YAP) phosphorylation, and increased YAP activity via Rho GTPase [42]. Pang et al reported that thrombin-induced RhoA and Rac1 activation could be significantly inhibited by ALEX1 overexpression, which indicated that ALEX1 could inhibit tumor metastasis through the PAR-1/Rho GTPase signaling pathway [43]. The PI3K pathway plays pivotal roles in many essential cellular processes including cell growth, differentiation, invasion, metastasis, and resistance to chemotherapy [5].…”
Section: Topological Analyses Of the Gc Related Lncrna-mrna Networkmentioning
confidence: 99%
“…Fujimoto et al reported that PAR1 induced GC cells to become stem-like, inhibited yes-associated protein (YAP) phosphorylation, and increased YAP activity via Rho GTPase [42]. Pang et al reported that thrombin-induced RhoA and Rac1 activation could be significantly inhibited by ALEX1 overexpression, which indicated that ALEX1 could inhibit tumor metastasis through the PAR-1/Rho GTPase signaling pathway [43]. The PI3K pathway plays pivotal roles in many essential cellular processes including cell growth, differentiation, invasion, metastasis, and resistance to chemotherapy [5].…”
Section: Topological Analyses Of the Gc Related Lncrna-mrna Networkmentioning
confidence: 99%
“…Thrombin-activated PAR-1 induces EMT (epithelial-mesenchymal transition, EMT) in gastric cancer cell lines [ 80 ]. Overexpression of NF-κB, EGFR, and TN-C also activated PAR-1 expression, which in turn promoted gastric cancer cell growth and invasion [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeted GTPase therapy is also being explored. For example, ALEX1 functions in gastric cancer through the PAR-1/Rho GTPase signaling pathway, becoming a new target for tumor inhibition [32]. RhoA-mediated Fbxw7 regulates the apoptosis of tumor cells and other phenotypes in gastric cancer [33].…”
Section: Discussionmentioning
confidence: 99%